Sal003 alleviated intervertebral disc degeneration by inhibiting apoptosis and extracellular matrix degradation through suppressing endoplasmic reticulum stress pathway in rats - Chen, Yan; Li, Baixing; Xu, Yue; Zhou, Tangjun; Zhao, Changqing; Zhao, Jie (Frontiers in Pharmacology, 2023)
Apoptosis and extracellular matrix degradation of the nucleus pulposus are the main initiators of intervertebral disc degeneration (IVDD) and can be explained by endoplasmic reticulum (ER) stress. Thus, pharmacological therapy aimed at suppressing this pathway may be a promising approach for the management of IVDD. In this study, we aimed to explore the protective effects of Sal003 against IVDD and its underlying mechanisms. Thapsigargin (Tg)-stimulated rat nucleus pulposus cells and a needle puncture-induced IVDD rat model were used to explore the protective effects of Sal003. Our results showed that Sal003 inhibited apoptosis and extracellular matrix degradation by suppressing the ER stress pathway. The therapeutic effects of Sal003 were also observed in the IVDD rat model, as evidenced by improved degeneration along with decreased apoptosis and extracellular matrix degradation in intervertebral discs. Our results demonstrated Sal003 as a potential treatment for IVDD.